Natural resource-seeking FDI inflows and current account deficits in commodity-producing developing economies (2017)
Natural resource-seeking foreign direct investment (FDI) rose substantially during the last two decades as global commodity prices soared. This type of FDI typically is expected to improve the current accounts of recipient countries. Notwithstanding the commodity boom, however, current account balances of many commodity-producing developing economies were negative during 1995–2013. Considering 31 commodity-producing countries, we find that the average net effect of a 1% increase in natural resource-seeking FDI was a 0.23% decline in the current account (measured as percentage of GDP). This surprising result can be explained by the repatriation of profits.